ANALYSIS OF THE POTENTIAL OF COASTAL WATERS FOR MARINE ECOTOURISM DEVELOPMENT IN PENYENGAT ISLAND RIAU ISLAND PROVINCE - Jung jung Maranata; Dessy Yoswaty; Afrizal Tanjung (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
Abstract               Ecotourism tourism is related to nature related to the knowledge and understanding of the natural environment and managed by the principles of sustainable development. This research was conducted in September - November 2017 at Penyengat Island, City of Tanjung Pinang, Riau Island Province. The study aims to determine the potential of marine ecotourism and aspects of the strength of Penyengat Island to be developed as a marine ecotourism area. The method used in this research is survey method and station point determination by purposive sampling. Value The results of the calculation of the value of the index the suitability of the Tour amounted to 80,77% (Station I), 80.77% (Station II), 82.69% (Station III), and 80.13% (Station IV). Assessment of strengths, weaknesses, opportunities, and threats, the development of Penyengat Island coastal potential was assessed from observations at research sites, interviews and questionnaires.             Penyengat Island has the potential as a marine ecotourism area such as the beauty of nature, mangrove forests, seagrass, coral reefs, and distinctive marine biota. The development of Marine Tourism in Penyengat island can be done with 1) The arrangement of the area by forming a system of zoning for marine tourism activities and the activities done by the society on the activity of the ecotourism beach and the management of the coastal environment, 2) improve the promotion of national and international scale; and 3) The preparation of spatial planning or zoning access with a variety of related institutions and local communities.Keywords: Potential, Marine Ecotourism, SWOT Analysis, Penyengat Island